Penerapan Metode Design Thinking pada UI/UX Website SaveBite untuk Penjualan Sisa Makanan dalam Mengurangi Food waste - Muhammad Sulthon Abdillah; Farel Atalla Muhammad Dafa; Ina Sholihah Widiati (Router : Jurnal Teknik Informatika dan Terapan, 2024)
In the rapid development of the food and beverage industry, overproduction and unsold food have led to a high amount of food waste, making Indonesia one of the largest food waste producers in the world. Data from the Central Bureau of Statistics (BPS) in 2021 shows that Indonesia produces 23-40 million tons of food waste annually, which negatively impacts the environment, natural resources, and the economy. This research aims to create a website that serves as a platform for selling leftover food to reduce food waste issues in Indonesia. The method used in designing this website is the Design Thinking method, which consists of five stages: Empathize, Define, Ideate, Prototype, and Test. Data for this method is collected through surveys and interviews with respondents. By creating this website, it is hoped to connect food business operators, such as restaurants, cafes, and bakeries, with consumers, allowing them to interact and providing an effective solution to reduce food waste in Indonesia. Additionally, it is expected that this website can minimize the waste of still-edible food for everyone. By ordering through this online platform, customers can get food at half the normal price.